A Unique Benthic Microbial Community Underlying the Phaeocystis antarctica-Dominated Amundsen Sea Polynya, Antarctica: A Proxy for Assessing the Impact of Global Changes - Cho, Hyeyoun; Hwang, Chung Yeon; Kim, Jong-Geol; Kang, Sanghoon; Knittel, Katrin; Choi, Ayeon; Kim, Sung-Han; Rhee, Sung-Keun; Yang, Eun Jin; Lee, SangHoon; Hyun, Jung-Ho (Frontiers in Marine Science, 2020)
Polynyas in the polar seas are regarded as windows through which ecosystem responses associated with global climate changes are to be noticed. However, little information is available on benthic microbial communities in the Amundsen Sea polynya (ASP), where environmental changes due to global warming are occurring rapidly, from which future climate change-induced ecosystem responses could be assessed. We performed high-throughput sequencing of 16S rRNA genes and quantitative PCR in combination with biogeochemical analyses and metabolic rate measurements to determine the composition, diversity and controls of major microbial communities in sediments of the ASP. A large fraction of the sequenced benthic microbial community (40% on average) in the polynya was uniquely affiliated with the phylum Planctomycetes, whereas Thaumarchaeota (51% on average) predominated in non-polynya areas. The relative abundance of Planctomycetes correlated significantly with organic carbon (Corg) content in the polynya sediment underlying the Phaeocystis-dominated water column. These results suggest that Planctomycetes comprise a major bacterial group utilizing relatively recalcitrant Corg produced primarily by Phaeocystis blooms. In contrast, the predominance of chemolithoautotrohic Thaumarchaeota in the sea-ice zone was attributed to low Corg supply due to low primary productivity in the ice-covered water column. The Planctomycetes-dominated microbial communities in the ASP is in stark contrast to that Proteobacteria (Delta- and Gammaproteobacteria) occupy ecological niches as primary mineralizers of organic materials in most benthic systems in the Southern Ocean, where organic materials in the sediments mostly originate from diatom blooms. Given that microbial communities respond quickly to environmental changes, and that global climate change is proceeding rapidly in the ASP, our results suggest that any modifications in the Planctomycetes-dominated microbial communities will provide valuable insight into changes in organic matter transport to the seafloor that may result from shifts in planktonic communities from Phaeocystis to diatoms associated with climate change.